Andaliman fruit (Zanthoxylum acanthopodium dc) from Sumatera can help reduce blood glucose: Glucose tolerance test - Mutia Salsabila Rosyianti; Isyah Radhiyah Saidek; Nindya Nur Amalina; Regalita Novia; Dhigna Luthfiyani Citra Pradana (Indonesian Journal of Health Science, 2026)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia due to impaired insulin secretion or action. The utilization of natural products as antihyperglycemic agents continues to be explored, including andaliman fruit (Zanthoxylum acanthopodium DC.), an endemic plant from Sumatra known to contain bioactive compounds such as flavonoids and saponins. This study aimed to evaluate the antihyperglycemic potential of ethanolic extract of andaliman fruit using an oral glucose tolerance test in male mice. An experimental design was applied with three groups: negative control (distilled water), positive control (glibenclamide), and ethanolic extract of andaliman fruit at a dose of 20 mg/kgBW. Blood glucose levels were measured before and after glucose induction up to 90 minutes. Data were analyzed using One Way ANOVA followed by the Bonferroni post hoc test. The results demonstrated a significant difference among treatment groups (F(2,6) = 19.344; p = 0.002). Post hoc analysis revealed that the andaliman extract significantly differed from the negative control (p = 0.024), but showed no significant difference compared to glibenclamide (p = 0.196). In conclusion, the ethanolic extract of andaliman fruit exhibits antihyperglycemic potential with statistically comparable effectiveness to glibenclamide in a glucose tolerance model. These findings support further development of andaliman as a potential phytopharmaceutical antidiabetic agent derived from local natural resources.